Banten Coffee Marketing Strategy for Putra Banten UKM Based on Blue Ocean Strategy - Setiawan, Johan; Nazhif, Naufal; Andi, Andi (Management Science Research Journal, 2023)
Coffee is one of the plant commodities that can grow in Banten, namely robusta coffee. Along with the development of people's lifestyles, it encourages new habits, namely the habit of consuming coffee. UKM Putra Banten is a production house that produces coffee products. Banten has the potential in marketing coffee commodities. However, there are obstacles faced by UKM Putra Banten, the obstacle is the difficulty of competing in existing market space. This study discusses the challenges of competition in the coffee industry and the right conversion strategy for marketing Kopi Banten by formulating the Blue Ocean Strategy. The research’s type is quantitative descriptive research and the data analysis method used the Blue Ocean Strategy method. The results showed that the competition in the coffee industry in the cities of Serang and Cilegon was included in the red ocean situation. The right strategy based on the Blue Ocean Strategy for Kopi Banten is formulated based on the formulation of four steps, namely (1) eliminate factors of coffee variants and types of coffee, (2) reducing factors ease of consuming coffee and inter-distribution systems, (3) increasing factors coffee taste, coffee aroma, hygiene, attractive packaging design, famous coffee brand, product information and sales contract system, and (4) addition of product items, online marketing and cooperation with coffee shops.